y+y-y-y+y-1=18

Simple and best practice solution for y+y-y-y+y-1=18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y+y-y-y+y-1=18 equation:


Simplifying
y + y + -1y + -1y + y + -1 = 18

Reorder the terms:
-1 + y + y + -1y + -1y + y = 18

Combine like terms: y + y = 2y
-1 + 2y + -1y + -1y + y = 18

Combine like terms: 2y + -1y = 1y
-1 + 1y + -1y + y = 18

Combine like terms: 1y + -1y = 0
-1 + 0 + y = 18
-1 + y = 18

Solving
-1 + y = 18

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + y = 18 + 1

Combine like terms: -1 + 1 = 0
0 + y = 18 + 1
y = 18 + 1

Combine like terms: 18 + 1 = 19
y = 19

Simplifying
y = 19

See similar equations:

| -93-4v=-10v+3 | | 2x^4-9x^2-16x=0 | | 3h+3h-6h+2j-2=12 | | 2x^4-9x^2-16=0 | | 18j+2j-10j-5j-4j=16 | | 18j+2j-10-5j-4j=16 | | 13p-6p-5p=18 | | 9t+(3f)t+13= | | 27-×/4=x/5 | | 4+7x-3=9x+13-6x | | 6j+-2j+14j-7j+-9n-(-19)=-15 | | m(a+5)=Kfora | | -0.1x^2-x+31=0.1x^2+2x+11 | | 6j+-2j+14j-7j+-9-(-19)=-15 | | 0.2x^2+x-20=0 | | 6j+-2j+14j-7j+(-19)=-15 | | 6j+2j+14j-7j+(-19)=-15 | | r-r+5r-2r=9 | | -5c+14c+-7=11 | | 5b-19b-(-20b)-(-14)=-10 | | 32+0.90m=2(31+0.30m) | | 20m-10m+2m-8m+2m=6 | | 5u+4u-6u-u=12 | | n^2-n-480=0 | | log(base)2(x^2-3x-66)=2 | | 20n-12n+-9n=8 | | 2x=17+2 | | -3h+-h+6h+-7h=15 | | 5x+26=10x-10 | | -3h+-h+6h+7h=15 | | 8x-4+4x+28=5x+10 | | 2y=3+6y |

Equations solver categories